Body Art - Thomas, Nicholas, 1960- (London Thames and Hudson, 2014)
Body art, practised across all world cultures and throughout history, is the most intimate art form, linking the self, the senses, and the social and political. In recent years, it has proliferated in an unprecedented way, borrowing motifs and practices from many different traditions. This book deals with this topic.
Include Index and Illustration
Keywords: Tattooing -- Body art -- Body marking